Structural characteristics of phycobiliproteins from red alga Mazzaella japonica. Issue 1 (27th September 2017) - Kitade, Yumi; Miyabe, Yoshikatsu; Yamamoto, Yohei; Takeda, Hirohumi; Shimizu, Takeshi; Yasui, Hajime; Kishimura, Hideki
Abstract: We determined the primary structures of phycoerythrin (PE), phycocyanin (PC), and allophycocyanin (APC) from red alga Mazzaella japonica . The phycobiliproteins consist of α‐ and β‐subunits like other red algae. M. japonica phycobiliproteins all conserved Cys residues for chromophore attachment site. The amino acid sequences of M. japonica phycobiliproteins showed considerably high identities with those of other red algae (81–100%). In addition, the sequences (YRD, LDY, LRY, VY, LF, and FY), which were angiotensin I converting enzyme (ACE) inhibitory peptides from other algae were detected in the primary structures of M. japonica phycobiliproteins. Then, we prepared the protein hydrolysates from M. japonica and measured its ACE inhibitory activity. Consequently, M. japonica protein hydrolysates indicated considerably high ACE inhibitory activity. Practical applications: M. japonica is an abundant resource in Japan, which contains a lot of phycobiliproteins. Then, M. japonica protein hydrolysates strongly inhibited the activity of ACE. Therefore, it has the potential to be an ingredient of functional food.